PRELIMINARY STUDY ON URINARY INFECTION IN PATIENTS WITH PREMATURE - Távara, Luis (2015)
50 cases of patients who had preterm labor is studied. Careful not to include cases where the cause of prematurity was evident (twins, polyhydramnios, hemorrhagic cases) were reported. Urine culture sample was taken by bladder catheterization in the first 48 hours postpartum. Parallel monitoring 50 cases of patients whose delivery was at term, and also was made urine culture is studied. It was obtained obvious differences in both groups. In the group studied was 20% positive urine cultures, against 10% in the control group. The predominant germ was E. coli. The perinatal mortality in the study group was 20%, ten times higher than the control group. It is recommended that urine cultures routinely performed in all cases of preterm labor.